Using the Strategy of Multi-Cloud Solutions for Environmental Protection - Dovgal Vitaly; Kuizheva S. (Russian Journal of Earth Sciences, 2023)
This paper discusses several extremely promising applications of multi-cloud solutions that can help achieve environmental protection and sustainability goals, provide ecological benefits, and aid wildlife research, conservation and protection. The widespread adoption of multi-cloud strategies helps illustrate the range of initiatives and approaches to reduce environmental burdens employed by government agencies, non-governmental organizations, and private companies.